Prenatal Exposure to Androgens and Gender Socialisation Effects on Children's Academic Interests - Laia Sánchez Guerrero; Pia S. Schober; Birgit Derntl (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Previous studies have documented gender differences in fields of study as well as interest in school subjects. Boys are on average more interested in mathematics, and girls show greater interest in languages. The extent to which these disparities are the result of biological or environment influences is still an open debate. On the one hand, brain organisation theory suggests that physiological and behavioural differences may be linked to prenatal hormone levels. On the other hand, sociological and psychological perspectives highlight the importance of gender socialisation. This paper combines biological, psychological, and sociological perspectives to examine the emergence of gendered academic interests in children. The study draws on data from 9‑year-old children from the Avon Longitudinal Study of Parents and Children (ALSPAC). Our results suggest that for both boys and girls, medium to high compared with low prenatal exposure to circulating maternal testosterone might increase children's interests in mathematics relative to English, although results vary depending on how prenatal testosterone exposure is measured. As the distributions of prenatal androgen exposure and the relationships with maths versus English interests are very similar for boys and girls, prenatal androgen exposure does not contribute to explaining gender differences in academic interests. However, we find some evidence that the relationship with parental gender socialisation varies by prenatal androgen exposure. A~more gender-equal parental division of domestic work is more strongly associated with less gendered academic interests for girls with low prenatal androgen exposure and for boys with medium to high androgen exposure.
Keywords: 300; Academic interests; Testosterone; Gender role socialisation; Parental gender division of housework; Father involvement; ALSPAC; Akademische Interessen; Testosteron; Geschlechtersozialisation; Geschlechtsspezifische Aufteilung der Hausarbeit; Väterliche Kinderbetreuung